Electrochemical Performance of Lithium-Ion Hybrid Supercapacitors based on Activated Carbon and Nanoplatelet Li4Ti5O12 Insertion Electrode Synthesized by Nanoscission Technique. Issue 1740 (16th March 2015) - Singh, Sandeep; Rastogi, Alok C; Omenya, Fredrick; Whittingham, M Stanley; Lal, Archit; Upreti, Shailesh
ABSTRACT: Electrochemical performance of hybrid supercapacitor (HSC) utilizing surface sculpted Li4 Ti5 O12 (LTO) insertion electrode having nanoplatelet-like morphology and activated carbon (AC) electrode is investigated for energy storage application. Cyclic voltammetry (CV) at variable scan rates 0.5 to 60 mV.s -1 in the 0-3.2 V range show pseusocapacitive behavior and fast rate of current change indicating rapid Faradaic kinetics. Nyquist impedance study show charge transfer resistance due to kinetic effects of electron transfer and Li + de-intercalation process at the LTO anode. Low capacity (0.2 C-1C) charge-discharge (CD) curves show high Coulomb efficiency with marginal reduction at high 5-10 C rates due to irreversibility of adsorbed PF6 anions at the electrolyte-AC interface. Galvanostatic CD cycling tests over 50 cycles at different C-rates show decline in storage capacity due to electrode polarization effects. Reduction, broadening and shift of the Raman line at 678 cm -1 from Ti-O bonds in TiO6 octahedra after cycling indicates Li insertion reactions in functioning of hybrid supercapacitor. The hybrid supercapacitor cells have shown energy density, 29 Wh.kg -1 and power density, 350 W.kg -1 .